2011
DOI: 10.1159/000324683
|View full text |Cite
|
Sign up to set email alerts
|

Copy Number Variation Accuracy in Genome-Wide Association Studies

Abstract: Background/Aim: Copy number variations (CNVs) are a major source of alterations among individuals and are a potential risk factor in many diseases. Numerous diseases have been linked to deletions and duplications of these chromosomal segments. Data from genome-wide association studies and other microarrays may be used to identify CNVs by several different computer programs, but the reliability of the results has been questioned. Methods: To help researchers reduce the number of false-positive CNVs that need to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 58 publications
2
25
0
Order By: Relevance
“…[Thompson et al, 2011;Bush and Moore, 2012]; the higher odds ratios, if confirmed in independent cohorts, may support the general observations that CNVs associated with phenotypes confer a higher effect size than the SNP-based associations [Lin et al, 2011]. Common CNVs identified in this study (online suppl.…”
Section: Concordant Cnvs Identified By Nexus Cn and Partek Gs Algorithmssupporting
confidence: 85%
See 4 more Smart Citations
“…[Thompson et al, 2011;Bush and Moore, 2012]; the higher odds ratios, if confirmed in independent cohorts, may support the general observations that CNVs associated with phenotypes confer a higher effect size than the SNP-based associations [Lin et al, 2011]. Common CNVs identified in this study (online suppl.…”
Section: Concordant Cnvs Identified By Nexus Cn and Partek Gs Algorithmssupporting
confidence: 85%
“…However, we refrained from such assumptions, and as such many of the identified CNVs in our study or their potential concordances may have been underestimated in our analysis. This is true of any algorithm comparisons implemented thus far for CNV association analysis, as acknowledged by others [Grayson and Aune, 2011;Lin et al, 2011;Zhang et al, 2011;Cantsilieris et al, 2014;Castellani et al, 2014].…”
Section: Workflow For Cnv Analysis Using Partek Genomics Suite 66mentioning
confidence: 82%
See 3 more Smart Citations